2017
DOI: 10.1002/2017jg003769
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Production and Removal in the Sediments of Shanghai River Networks: Spatiotemporal Variations, Controlling Factors, and Environmental Implications

Abstract: Ammonium (NH4+) pollution and associated processes causing environmental problems in aquatic ecosystems have attracted much attention. However, the microbial pathways of NH4+ production and removal and associated influencing factors in the sediments of urban rivers remain unclear. In this study, microbial pathways of NH4+ production and removal were quantified to examine the NH4+ balance in the sediments of Shanghai river networks. The results indicated that potential rates of gross nitrogen mineralization, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…It has been reported that anaerobic respiration can tend to more accumulation of sulfide in organic matter‐enriched environments (Giblin et al, ; Jensen et al, ). Therefore, the inverse relationships of anammox with DOC and NH 4 + in our study may be attributed to the higher sulfide inhibition on anammox in the high DOC and NH 4 + content environments (Jensen et al, ; Lin et al, ). The partial correlation analysis controlling for sediment pH indicated that mean annual temperature had no significant influence on anammox rates, which in turn reflected the dominant role of pH in regulating anammox rates throughout the rivers.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…It has been reported that anaerobic respiration can tend to more accumulation of sulfide in organic matter‐enriched environments (Giblin et al, ; Jensen et al, ). Therefore, the inverse relationships of anammox with DOC and NH 4 + in our study may be attributed to the higher sulfide inhibition on anammox in the high DOC and NH 4 + content environments (Jensen et al, ; Lin et al, ). The partial correlation analysis controlling for sediment pH indicated that mean annual temperature had no significant influence on anammox rates, which in turn reflected the dominant role of pH in regulating anammox rates throughout the rivers.…”
Section: Discussionmentioning
confidence: 61%
“…However, denitrification, anammox, and DNRA exhibit different sensibilities in response to temperature changes. Previous studies reported that there was no significant seasonal difference in anammox rates, although the high anammox rates were observed in winter (Lin et al, ; Lisa et al, ). Anammox was not detected even in tropical estuarine sediments (Dong et al, ), further suggesting a limited effect of temperature on anammox.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A previous study reported that NH 4 + has a positive effect on Actinobacteria abundance, and NO 3 − shows a positive correlation with Armatimonadetes , Chloroflexi and Bacteroidetes abundances [14]. In addition, nitrogen transformation pathways in urban rivers have been reported to alter in response to the increasing nitrogen input from anthropogenic activities [17,18], which may be attributed to the shifts of bacterial community [6,19]. Although these studies have improved our understanding of the alterations in microbial community composition and nitrogen cycling under nitrogen pollution stress, knowledge of the dynamics of bacterial diversity and abundance in river sediments impacted by large amount of nitrogen inputs is still limited in the highly urbanized areas.…”
Section: Introductionmentioning
confidence: 99%